Direct production of activated carbon from coconut shell through chemical activation with ammonium chloride - Movillon, J. L.; Valencia, S. A.; Demafelis, R. B.; Matibag, E. V. (2001)
Coconut shell (containing 11.05% water, 63.20% volatile combustible matter, 1% ash, and 24.75% fixed carbon) was chemically activated with NH4Cl for 1 h at different temperature settings (400, 600, and 800 C) and at different NH4Cl-shell ratios (1:4, 1:6, 1:8). A laboratory-scale locally manufactured pyrolyzer was used in the chemical activation process. Based on carbon recovery and decolorizing capability, the optimum treatment combination for chemical activation of coconut shell is at 800 C and at a NH4Cl-shell ratio of 1:4.
Keywords: Activated carbon; Coconut husks; Pyrolysis; Gas absorption & adsorption